2020
DOI: 10.1103/physrevresearch.2.033371
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal phases with unusual structures and physical properties formed by acute-angle bent core molecules

Abstract: Liquid crystals formed by acute-angle bent core (ABC) molecules with a 1,7 naphthalene central core show an intriguing phase behavior with the nematic phase accompanied by poorly understood additional phases. In this work, we characterize the physical properties of an ABC material, such as birefringence, dielectric permittivities, elastic constants, and surface alignment and present x-ray diffraction and transmission electron microscopy studies of their ordering. The ABC molecular shape resembling the letter λ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…A strict comparison with experimental results is beyond the scope of this work, since the model used here (rigid particles interacting though a purely repulsive potential) lacks important elements for a proper description of thermotropic nematics made of flexible molecules. Nevertheless, it is interesting to see that for S around 0.4 ÷ 0.5, which appears reasonable for thermotropic systems, the anomalous order K 11 < K 22 < K 33 is found, which is in line with the experimental trend reported in [36], and the relative values of the three elastic constants are also comparable to the measured quantities.…”
Section: Acute Angle Particlessupporting
confidence: 86%
See 2 more Smart Citations
“…A strict comparison with experimental results is beyond the scope of this work, since the model used here (rigid particles interacting though a purely repulsive potential) lacks important elements for a proper description of thermotropic nematics made of flexible molecules. Nevertheless, it is interesting to see that for S around 0.4 ÷ 0.5, which appears reasonable for thermotropic systems, the anomalous order K 11 < K 22 < K 33 is found, which is in line with the experimental trend reported in [36], and the relative values of the three elastic constants are also comparable to the measured quantities.…”
Section: Acute Angle Particlessupporting
confidence: 86%
“…Negative p zZ values mean that the apex of a V-shaped particle preferentially points towards the center of the splay deformation (see Figure 1). Finally, Figure 6 collects the three Frank elastic constants of particles with bend angle χ = 45 • , which is close to the value of the apical angle in the molecules with 1,7-naphthalene central core investigated in Reference [36]. A strict comparison with experimental results is beyond the scope of this work, since the model used here (rigid particles interacting though a purely repulsive potential) lacks important elements for a proper description of thermotropic nematics made of flexible molecules.…”
Section: Acute Angle Particlessupporting
confidence: 63%
See 1 more Smart Citation
“…In recent decades, there have been an increased number of reports on anomalous LC properties caused by bent-shaped molecules. [10][11][12][13][14][15][16] Dorjgotov et al found much higher rotational and flow viscosities for a bent-core material than typical rodshaped calamitics. 17 As many groups reported, unlike common calamitic NLCs, the bend elastic constant K 33 is smaller than the splay elastic constant K 11 in bent-core materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the intermediate mesogenic properties of calamitic and bent-core LCs, they exhibit formation of distinct phases viz. dark conglomerate, 32–34 biaxial nematic, 35–37 twist-bend nematic 38–42 and cluster phases. 25,43,44 In the field of bent-core LCs, there are very few reports, mostly in a scattered way that describe “de Vries-like” characteristics.…”
Section: Introductionmentioning
confidence: 99%